ANALISIS KESULITAN BELAJAR PADA PELAJARAN EKONOMI X IPS DI SMA NEGERI 1 SUNGAI RAYA - Diana Vita; F.Y Khosmas; Achmadi Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This study aims to determine the factors that cause learning difficulties in economic subjects in class X IPS at SMA Negeri 1 Sungai Raya. The research method used is descriptive with a qualitative research form. The results showed that: 1.Internal physiological factors of health are the first and main factors that must be maintained so that the learning process can run well. 2.Internal psychological factors are devided into three, namely the intelligence of students who experience economic learning difficulties is still lacking, students interest is still lacking. 3.External factors of the family environment are lack of attention from parents at home due to busy work. 4.Extrnal factors of the school environment are divided into two, namely teacher teaching methods, lack of teacher creativity in using teaching methods. The students school discipline is very lacking because when the teacher explains, many students are still chatting and playing. 5.Factors that cause the community environment, namely friends hanging out are very important because if friends hanging out is bad it will have a bad impact and vice versa. Keywords : Factors causing learning difficulties